The investigation of an inexpensive infra-red camera based building monitoring system for the aid of efficient building development - Vorajee, Naadir M (Department of Electrical Engineering, 2020)
As the world is moving toward a greener, more sustainable future, the use of HVAC (Heating, Ventilation and Air-conditioning) systems are detrimental toward providing more efficient structures. Current UAVs (Unmanned Aerial Vehicle) used for surveying purpose are highly priced, with costs ranging upwards of R25 000. In this project, we propose a possible cost effective solution, with a budget of R10 000, that can be used in order to accurately survey a building for cracks and thermal inefficiencies within the envelope of the building. The project proposes a low cost Thermal camera to be used for the surveying as well as a validation of thermal camera for temperature reading. The project also proposes a low cost drone to be used for the possible prototype. The project follows a typical engineering design approach, specifically via the use of a V-model for the thermal camera used for image processing. After the constraints and requirements were defined, the engineering design commenced with a careful selection of both the IR camera and drone to be used for the possible prototype. Thereafter, experiments were set up to validate the use of the drone and IR camera as a viable option as a tool for building envelope surveyance. There were 6 experiments that were recorded during the process of this project. Firstly as statistical validation occurred through four tests whereby the thermal camera was validated with a mercury thermometer for temperature measurement. The second experiment was focused on the capability of the thermal camera to detect anomalies in a structure. This experiment made use of 3 holes of varying size drilled into a ceramic material with a heat source behind. Thermal images were then taken at various distances and then processed accordingly. The third experiment was focused on the ability to detect the area of the anomaly given a known distance from the thermal camera to the anomaly. The experiment followed the same set-up as described in the second experiment, however instead of 3 holes of varying size, only one hole was used. The fourth experiment looked at the building envelope and was focused on developing an algorithm to calculate the weighted average of the temperature of the structure rather than using the given structure temperature at a single point. In addition, the experiment qualitatively showed a difference between new and older insulation types. The fifth experiment focused on the development of an algorithm that would result in automatic image segmentation. The sixth experiment focused on the low cost drone and its ability to be used to survey a building. All experiments were successfully carried out. The thermal camera was validated as a reliable source for temperature measurement and could be used to detect anomalies as small as 3mm in diameter from a distance of 750mm from the target. In addition, an algorithm was developed that could be used to automatically tell the user the area of the anomaly with a 95% accuracy in certain cases. An algorithm was also developed to indicate the weighted mean temperature of an area of a building envelope. Lastly, the drone was successfully used to survey a building via the use of a developed protocol.